Kinetics of pyrite oxidation in simulated mine tailings pond conditions - Nablo, Geoffrey Ray L.
Pyrite oxidation is the predominant source of acid mine drainage (AMD), which is one of the severe environmental impacts of mining. AMD destroys flora and fauna in the nearby ecosystem, and it causes grave health problems to the people. To further the understanding and help in the mitigation of AMD, this electrochemical study investigates the effect of the electrolyte pH, type and concentration of oxidant, agitation, presence of chalcopyrite and, aging to the rate of pyrite oxidation, while simulating the conditions in tailings ponds. Open Cell Potential (OCP) and Electrochemical Impedance Spectroscopy (EIS) analysis were done using a three-electrode cell set-up, which is composed of a pyrite rotating disc electrode (RDE), mercury/mercurous sulfate reference electrode in saturated potassium sulfate, and a platinum counter electrode, with a sulfuric acid working electrolyte. Polarization resistance obtained after fitting an electrical circuit to the EIS data was related to the rate of pyrite oxidation, while OCP was used to describe its oxidation mechanism. It was found out that the oxidation of pyrite by dissolved oxygen was the mechanism occurring in all the experiments, except when ferric and chalcopyrite were added. The parameter setting with the lowest relative oxidation rate were: electrolyte at pH 4, with no ferric addition, and with nitrogen purging; RDE at 400 RPM, with 10% chalcopyrite addition, and 7 hours aging. Reaction orders calculated for the effect of ferric and hydrogen ions were equal to 1, while 0.5 was obtained for oxygen. Presence of chalcopyrite in the RDE caused the preferential oxidation of chalcopyrite instead of the pyrite due to their galvanic interaction. A shift in the rate determining step from a chemical reaction to diffusion control was observed after aging the electrode for 3 hours and beyond as a consequence of the thickening sulfur product layer. The presence of the product layer resulted in a 9-fold decrease in the oxidation rate of pyrite.